Eschatology : Biblical, historical, and practical approaches : a volume in honor of Craig A. Blaising - Blaising, Craig A. (Kregel Academic, 2016)
"Thirty evangelical scholars, writing for the student, the pastor, and the church at large, examine a crucial and, for some Christians, a contentious doctrine of Scripture. Reflecting various points of view while avoiding a sectarian tone, Eschatology presents an accessible overview of the doctrine of the future and its implications for believers today. Each of the four sections moves the reader toward an evangelical, holistic, integrative, and systematic perspective on the doctrine of the future. Whether used as an introductory textbook or as a resource for spiritual growth, this volume - biblical, thoughtful, and practical - combines the best elements of doctrine"--Back cover